YOUTH SLANGS IN MODERN AMERICAN AND BRITISH ENGLISH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article contains an annotated bibliography of the slang used by young people, and specifically the slang of students, in both Britain and the United States. In addition, there is a brief account of the English influences on foreign youth slang. Some introductory remarks on the expressive nature of the language of such groups are also made.